2011
DOI: 10.4103/0970-2113.80319
|View full text |Cite
|
Sign up to set email alerts
|

Role of percutaneous closed needle pleural biopsy among patients of undiagnosed exudative pleural effusion

Abstract: Background:Sometimes etiological diagnosis of pleural effusion is difficult despite cytological, biochemical and microbiological tests and labeled as undiagnosed exudative pleural effusions.Aim of present study was to make an etiological diagnosis of pleural effusion.Materials and Methods:Study group included patients of exudative pleural effusion where etiological diagnosis could not be yielded by conventional cytological, biochemical and microbiological investigations. Pleural tissue was obtained by Cope’s p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 17 publications
2
14
1
Order By: Relevance
“…25 Blind pleural biopsy was nonrepresentative in 15.5% patients who underwent CBPB, and similar rates of nonrepresentative samples with blind pleural biopsies have been reported in other studies also. 3,15 Pleural biopsies could not be obtained in 6.8% of the patients undergoing MT in this study, and is marginally higher than the earlier reported rates. 13,14 This is probably due to the delayed presentation of patients to our center, which led to the formation of multiple pleural adhesions.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…25 Blind pleural biopsy was nonrepresentative in 15.5% patients who underwent CBPB, and similar rates of nonrepresentative samples with blind pleural biopsies have been reported in other studies also. 3,15 Pleural biopsies could not be obtained in 6.8% of the patients undergoing MT in this study, and is marginally higher than the earlier reported rates. 13,14 This is probably due to the delayed presentation of patients to our center, which led to the formation of multiple pleural adhesions.…”
Section: Discussioncontrasting
confidence: 82%
“…Hence, in many centers, CBPB continues to be performed in the workup of undiagnosed EPE. 6,[15][16][17] In this retrospective study, we describe our experience with MT and also compare the outcome of thoracoscopy (both rigid and semirigid) with that of CBPB.…”
mentioning
confidence: 99%
“…In the present study as well in 94.4% of malignant pleural effusions, ADA levels were below 40 IU/L. [25121314] However, two patients (5.6%) had ADA levels 46.2 IU/L and 46.7 IU/L respectively who were diagnosed to have malignancy on pleural biopsy subsequently.…”
Section: Discussionsupporting
confidence: 42%
“…Percutaneous closed pleural biopsy was done in 108 and was positive in 53 (49%) cases. A closed needle biopsy of the pleura has been found to be very useful in cases of undiagnosed exudative pleural effusion,[ 16 ] as it reaches a specific diagnosis in a majority of the cases, causes little morbidity or mortality, and can be performed with little instrumental and manpower support. This is of importance in a developing country like India where the facilities of thoracoscopy and imaging-guided cutting needle biopsies are not easily available.…”
Section: Discussionmentioning
confidence: 99%